Estudo e desenvolvimento de antenas de microfita utilizando tecido de malha a base de fibras têxteis compostas - Holanda, Samanta Mesquita de (Universidade Federal Rural do Semi-Árido, 2016)
The growing development of telecommunications, especially mobile devices, has intensified related searches the microstrip antennas in recent years since they have unique properties and wide range of applications. The constant demand for lighter and more flexible devices boosted research in wearable technology area where electronics are fully embedded in their fibers. In this context, knitted fabrics have the necessary elasticity to create adaptable and sports parts, enabling high mobility and comfort to its users. The textile antennas are malleable and, therefore, have great utility in applications where rigidity of traditional antennas is considered limiting, as in military use clothing and in the biomedical field. This work aims to study and develop microstrip antennas using knitted fabric based composite fibers, showing the procedures and materials used from the characterization and choice of fabrics to the design, manufacture and testing of the textile antenna. The electrical characterization was carried out using a Vector Network Analyzer (ARV) to obtain the electrical properties (permittivity and tangent losses). Obtaining textile properties (weight, dimensional stability, degree and tensile strength) was made in accordance with the technical standards, using the equipment available at the Department of Textile Engineering at the Federal University of Rio Grande do Norte (UFRN). The antenna has been designed using the transmission line model of Fortran program developed in accordance with the electrical properties of textile substrates. Subsequently the antenna was designed and simulated in HFSS® (High Frequency Structural Simulator), where radiation patterns are obtained, return loss, the Smith chart, current density and gain. The best simulated result was implemented with tissue disposed knitted in a three-layer structure according to the dimensions designed, and then the antenna is tested using a spectrum analyzer, which were collected data that allowed the manufacture of the letter Smith and graph of return loss. The experimental data were compared with the simulated and the results analyzed according to the literature that support this paper
Study and development of microstrip antennas using knitted fabrics based on composite textile fibers
Keywords: Antenas de microfita; Antenas têxteis; Tecido de malha; Microstrip antennas; Antennas textiles; Knitted fabric; ENGENHARIAS::ENGENHARIA ELETRICA